Inhaled Budesonide and Oral Dexamethasone Prevent Acute Mountain Sickness - Zheng, Cheng-Rong; Chen, Guo-Zhu; Yu, Jie; Qin, Jun; Song, Pan; Bian, Shi-Zhu; Xu, Bai-Da; Tang, Xu-Gang; Huang, Yong-Tao; Liang, Xiao; Yang, Jie; Huang, Lan (The American journal of medicine, 2014)
This double-blind, randomized controlled trial aimed to investigate inhaled budesonide and oral dexamethasone compared with placebo for their prophylactic efficacy against acute mountain sickness after acute high-altitude exposure. There were 138 healthy young male lowland residents recruited and randomly assigned to receive inhaled budesonide (200 μg, twice a day [bid]), oral dexamethasone (4 mg, bid), or placebo (46 in each group). They traveled to 3900 m altitude from 400 m by car. Medication started 1 day before high-altitude exposure and continued until the third day of exposure. Primary outcome measure was the incidence of acute mountain sickness after exposure. One hundred twenty-four subjects completed the study (42, 39, and 43 in the budesonide, dexamethasone, and placebo groups, respectively). Demographic characteristics were comparable among the 3 groups. After high-altitude exposure, significantly fewer participants in the budesonide (23.81%) and dexamethasone (30.77%) groups developed acute mountain sickness compared with participants receiving placebo (60.46%) (P = .0006 and P = .0071, respectively). Both the budesonide and dexamethasone groups had lower heart rate and higher pulse oxygen saturation (SpO2) than the placebo group at altitude. Only the budesonide group demonstrated less deterioration in forced vital capacity and sleep quality than the placebo group. Four subjects in the dexamethasone group reported adverse reactions. Both inhaled budesonide (200 μg, bid) and oral dexamethasone (4 mg, bid) were effective for the prevention of acute mountain sickness, especially its severe form, compared with placebo. Budesonide caused fewer adverse reactions than dexamethasone.